Consistency between Itinerant and Local-Moment Pictures for Superconductivity in Alkaline Iron Selenide Superconductors - 李海超 向圆圆 王强华 (Chinese physics letters, 2014)
We study the superconducting pairing in an effective one-orbital model for alkaline iron-selenide superconductors. In both itinerant and local-moment pictures, we find that the nearest-neighbor hopping t1 plays a crucial role. The pairing symmetry changes from s-wave to d-wave as t1 is enhanced. For a reasonable t1 relevant to the experiment, the pairing symmetry is s-wave in both pictures, in agreement with the angle-resolved photo-emission. The results resolve the previous theoretical inconsistency in the two pictures.